L’exploitation financière des secteurs populaires argentins - Pablo Ignacio Chena; Alexandre Roig (Revue de la Régulation)
The workers autonomy in popular economy is challenged by the financial relationships in which they are inserted. This article focus in the way in which financial exploitation destabilizes the attempt to build the popular economy as social class. In this context, we analyzes the financial relationships that characterize the access to consumption in Argentinean popular sectors to show that they are performative of a new form of economic exploitation that we called « financial exploitation ». This phenomenon differs from the traditional processes of financialization because it is not reflected in the household over-indebtedness, but in the use of the interest rate levels (absolute and relative) as the main mechanism to transfer the economic surpluses and to create a social hierarchy.Without trying to reduce the popular economy to pre-existing categories, this work describes this category how it’s claimed by the workers themselves: the way in which they identify their economic practices, how they build their social mobilization and by their representation form. We will show that financialization not replace the labor relations in the decoding of contemporary capitalism. These two relations, labor and finance, are combined, not so much in the light of the rate of profit that capitalist expect, but around the interest rate. In this sense, financial exploitation objectifies a social class whose position is revealed by a differential of interest rate in relation to other classes. The relationship of domination is between creditor and debtor. At the same time, and with the ambiguity that the debt has in this point, a part of the population access to durable goods thanks to financialized consumption. In Polanyan terms, the interest rate is the new steam engine of financial capitalism. It produces the great differentials of the primitive accumulation and hierarchizes the world, taking in priority those that control the technologies of production of interest rates.